Analisis Indeks Kepuasan Masyarakat (IKM) Terhadap Kualitas Pelayanan Pada PT. PLN (Persero) - Mustamin; Nazwin, Asfarony Hendra; M. Wahyullah (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This study aims to measure the level of public satisfaction with the quality of service provided by PT. PLN (Persero), using the Sape Customer Service Unit in Bima Regency as a case study. Employing a survey method with a questionnaire as an instrument, this research analyzes nine aspects of service, including facilities and infrastructure, employee behavior, and service completion time. The data analysis technique used questionnaire data with a Customer Satisfaction Survey (CSS) analysis based on the Indonesian Minister of Administrative and Bureaucratic Reform Regulation No. 14 of 2017. The results show that overall, from the nine service elements, the Public Satisfaction Index for PLN Sape services is categorized as Good with a conversion value of 80.08%. The most satisfying aspect is facilities and infrastructure with a conversion value of 85.25%, while the lowest is employee behavior at 76.75%, making it the most dominant factor influencing the level of satisfaction. These findings provide recommendations for PLN management to improve the quality of service to meet public expectations and increase customer satisfaction. This study is expected to serve as a reference for further studies on public satisfaction with electricity services.